Targeting Chemokines and Chemokine Receptors in Melanoma and Other Cancers - Jacquelot, Nicolas; Duong, Connie P. M.; Belz, Gabrielle T.; Zitvogel, Laurence (Frontiers in Immunology, 2018)
The tumor microenvironment is highly heterogeneous. It is composed of a diverse array of immune cells that are recruited continuously into lesions. They are guided into the tumor through interactions between chemokines and their receptors. A variety of chemokine receptors are expressed on the surface of both tumor and immune cells rendering them sensitive to multiple stimuli that can subsequently influence their migration and function. These features significantly impact tumor fate and are critical in melanoma control and progression. Indeed, particular chemokine receptors expressed on tumor and immune cells are strongly associated with patient prognosis. Thus, potential targeting of chemokine receptors is highly attractive as a means to quench or eliminate unconstrained tumor cell growth.